Effects of Adding Seablite (Suaeda maritima) Leaves Powder on Textural and Sensory Properties of Chinese Steamed Bread - Bulan, Dusit; Tangcharoenbumrungsuk, Kamonwan; Kumchoo, Sakuntar (Journal of Home Economics Technology and Innovation, 2022)
The objective of this research aimed to study the effects of added seablite leaves powder at 0%, 2%, 4%, and 6% on the texture level properties and sensory acceptance of Chinese steamed bread. All data were analyzed by analysis of variance and the Duncan’s Multiple Range Test to determine multiple comparisons of mean values at the 95% confidence interval. The study results showed that the addition of seablite leaves powder in Chinese steamed bread tended to change preference score in terms of appearance, color, smell, taste, texture and overall preference was significantly decreased (p 0.05). When the amount of seabite leaf powder was increased, the color and texture characteristics of Chinese steamed bread were changed due to the green color and dietary fiber content of the seabite leaf by adding seabite leaf powder at the level of 4%. The tester accepted the score of 7.57 in the moderate level of preference. When tested for texture characteristics, it was found that the hardness was significantly increased (p<img title="<" src="https://latex.codecogs.com/gif.latex?<">0.05). The Seabite Chinese steamed bread recipe contains included Wheat flour 53.19 %, seabite leaf powder 3.83 %, yeast 0.74 %, baking powder 0.32 %, sugar 7.98 %, salt 0.43 %, water 30.85 %, and shortening 2.66 %.